2019
DOI: 10.1093/jac/dkz476
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study to determine the cefepime-induced neurotoxicity threshold in hospitalized patients

Abstract: Objectives Cefepime-induced neurotoxicity (CIN) has been demonstrated to be associated with cefepime plasma concentrations; however, the toxicity threshold remains unclear. The primary objective of this study was to identify the cefepime plasma trough concentration at which neurotoxicity occurs. Secondary objectives were to determine the incidence of CIN at a large tertiary institution and to identify patient factors associated with the development of CIN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 20 publications
6
36
0
Order By: Relevance
“…In our cohort, no patient presented a neurotoxicity related to cefepime with a probable or a certain causality according to the WHO-UMC system in contrast to the study by Lau et al [16]. All patients who experienced neurotoxicity were rated as only possible because the neurological adverse effect could also be explained by disease or other drugs, which is comparable with the findings of Huwyler et al and Boschung et al [14,15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our cohort, no patient presented a neurotoxicity related to cefepime with a probable or a certain causality according to the WHO-UMC system in contrast to the study by Lau et al [16]. All patients who experienced neurotoxicity were rated as only possible because the neurological adverse effect could also be explained by disease or other drugs, which is comparable with the findings of Huwyler et al and Boschung et al [14,15].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, a multidisciplinary meeting was organized to avoid discrepancy between assessors. Neurotoxicity related to cefepime remains a challenge to recognize especially in the critically ill population due to widely varying symptoms that are common in the intensive care unit; in this context we agree with Lau et al that the assessment of neurotoxicity requires further validation and standardization in future investigations [16,19].…”
Section: Discussionsupporting
confidence: 85%
“…90 In a small prospective study on piperacillin in hematological malignancies, no relationship was found between duration of fever, days to recovery from neutropenia, and achievement of PK/PD targets. 91 Regarding toxicity, cefepime plasma trough concentrations > 35 mg/L were related to neurotoxicity, 92,93 and it has even been suggested that for intermittent infusions trough concentrations > 20 mg/L should be avoided. 93 To assess the value of beta-lactam TDM and dose individualization regarding clinical outcome, randomized clinical trials are warranted and currently being conducted.…”
Section: Beta-lactamsmentioning
confidence: 99%
“…9, 14, 36, 37 Although many reports suggested that cefepime causes neurotoxicity and nephrotoxicity 38,39 , many reports showed that cefepime has little or no hepatotoxic effects, however other reports stated that cefepime-induced hepatotoxicity is rare and even it might not cause hepatotoxicity. 23,40 The results of the current study showed that cefepime had severe hepatotoxic effects at the levels of histological structures, liver enzymes as well as the mRNA expression of proinflammatory cytokines; such conflict whether cefepime causes severe liver injury, mild injury or even it is safe may be attributed to the idiosyncratic drug hepatotoxicity. 41 In the current study, the histopathological examinations of the liver of the cefepime treated rats as well as those treated with saline after cefepime showed marked hepatocellular degeneration, vacuolation, necrosis, nuclear pyknosis, fat cells formation, apoptosis, inflammatory cells infiltration and marked fibrosis in the portal areas.…”
Section: Discussionmentioning
confidence: 71%